AUDIT TENURE, KOMPLEKSITAS OPERASI, TOTAL ASET, DAN SOLVABILITAS SEBAGAI DETERMINAN AUDIT DELAY - Baqi Rizkinov; Sem Paulus Silalahi (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2021)
This study aims to determine the effect of audit tenure, operating complexity, total assets, and solvability on audit delay. This study uses a quantitative approach using secondary data contained in the company's Annual Report. The population in this study are mining companies listed on the Indonesia Stock Exchange for the 2017-2019 period. Through purposive sampling method, 36 companies were obtained as samples. The results of multiple linear regression analysis using SPSS 26 software show that the complexity of operations and solvability affect audit delay. Meanwhile, audit tenure and total assets have no effect on audit delay. The results of this study have a contribution to the companies in reducing the occurrence of audit delay.